Relationship Between Ferritin and Folic Acid Levels In Pregnant Women With Newborn Weight and Head Circumference - Usna Maria Harahap; Fadil oenzil; Desmawati Desmawati (Universitas Andalas, 2018)
Iron deficiency and folic acid anemia cause decrease in ferritin and folic acid levels that can interfere with the intake of oxygen and nutrients to the fetus resulting in LBW and reduced brain growth during pregnancy. The aim of the study was to determine the relationship between ferritin and folic acid levels in pregnant women with newborn weight and head circumference.This study was a cross sectional study conducted on 55 pregnant women at 37-42 weeks who were taken by consecutive sampling technique. The study was carried out in the Working Area of the Puskesmas and the Regional Health Laboratory of the Merangin Regency, and the health laboratory of West Sumatra Province from May 25 to July 13, 2018. Test the normality with the Kolmogorov-smirnov test and the correlation test using Pearson and Spearman.The results showed ferritin mean 23,643±16,682 ng/ml, folic acid 14,093±4,578 ng/ml, newborn weight 3047,27±399,005 gram and head circumference 33,02±1,163 cm. Statistical test results showed no correlation between ferritin levels with body weight (r=0.063, p=0.648) and head circumference (r=0.018, p=0.895) and folic acid levels with body weight (r=-0.036, p=0.795) and head circumference (r=-0.098, p=0.477).The conclusions of the study were that ferritin and folic acid levels of pregnant women had no significant correlation with newborn weight and head circumference. By improving nutrition, socioeconomic, qualitative antenatal care, initial referral of risky cases and supplementation of iron and folic acid can reduce the incidence of anemia.